LOCUS OF CONTROL, KETIDAKPASTIAN LINGKUNGAN DAN SISTEM AKUNTANSI MANAJEMEN - Sutapa .; R Erviana Y (Jurnal Bisnis dan Ekonomi, 2010)
The uncertainty of the existing environment will complicate managers in making of theplanning and exercise controlling on of the company's operations. Information was one of thepotential companies that have to received the attention of managers, because in addition to theoperation of information companies can also function as a tool to identification the relevantactivities of the company. Besides environmental uncertainty, information needs of a manageralso influenced by personality factors that of indicated with the locus of control. The problem inthis study is the locus of control the influence relationship of environmental uncertainty on thecharacteristics of management accounting systems information. Population in this researchmanager of manufacturing companies in Surakarta city and the sample of 76 respondents,meanwhile for the data analysis used Structural Equation Models. The use of model equationswith an application program "Partial Least Squares (PLS).The finding also indicated that thelocus of control not significant the relationship between of environmental uncertainty on thecharacteristics of management accounting systems broad scope, timelines and aggregation,meanwhile the locus of control significant the uncertainty of the environment on thecharacteristics of accounting integration systems. Information integration the showing that thereis coordination between the segments of one subunit with another. The complexities and relevancywith each other subunits will be reflected in the integrated. The more of segments in the subunitswithin the organization, so the information’s integrated ware very needed .Keywords: locus of control, environmental uncertainty, broadscope, timeless, integrated, agregate